DNA methylation patterns in the peripheral blood of Xinjiang brown cattle with variable somatic cell counts - Wang, Dan; Ma, Shengchao; Yan, Mengjie; Dong, Mingming; Zhang, Menghua; Zhang, Tao; Zhang, Tao; Zhang, Xiaoxue; Xu, Lei; Huang, Xixia (Frontiers in Genetics, 2024)
The use of wide-ranging dairy herd improvement (DHI) measurements has resulted in the investigation of somatic cell count (SCC) and the identification of many genes associated with mastitis resistance. In this study, blood samples of Xinjiang brown cattle with different SCCs were collected, and genome-wide DNA methylation was analyzed by MeDIP-seq. The results showed that peaks were mostly in intergenic regions, followed by introns, exons, and promoters. A total of 1,934 differentially expressed genes (DEGs) associated with mastitis resistance in Xinjiang brown cattle were identified. The enrichment of differentially methylated CpG islands of the TRAPPC9 and CD4 genes was analyzed by bisulfate genome sequencing. The methylation rate of differentially methylated CpGs was higher in the TRAPPC9 gene of cattle with clinical mastitis (mastitis group) compared with healthy cattle (control group), while methylation of differentially methylated CpGs was significantly lower in CD4 of the mastitis group compared with the control group. RT-qRCR analysis showed that the mastitis group had significantly reduced expression of CD4 and TRAPPC9 genes compared to the control group (P < 0.05). Furthermore, Mac-T cells treated with lipopolysaccharide and lipoteichoic acid showed significant down-regulation of the TRAPPC9 gene in the mastitis group compared with the control group. The identified epigenetic biomarkers provide theoretical reference for treating cow mastitis, breeding management, and the genetic improvement of mastitis resistance in Xinjiang brown cattle.